The estimated value can be given by 21.76
To solve this expression, let's just:
divide both terms between themselves, and then approximate the result.:[tex]\\\large \sf 102.3 \div 4.7 = 21.7659574468\\[/tex]
We can make the approximation to the first two numbers after the point, thus having the result
[tex]\red{\boxed{\large \sf \approx 21.76}}[/tex]
So, the answer will be 21.76
Answer:
20
Step-by-step explanation:
Determine the measure of the unknown labeled angles in the diagram above
Which of the following equations are equivalent to -2m - 5m - 8 = 3 + (-7) + m?
-15m = -4m
-7m - 8 = m - 4
-3m - 8 = 4 - m
m - 4 = -7m - 8
-8 - 7m = -4 + m
-8 - 3m = 4 - m
It's B)
Sorry... I was late
Answer:
-7m - 8 = m - 4
Step-by-step explanation:
Our original equation is
-2m - 5m - 8 = 3 + (-7) + m
Combining like terms on the left, we have
-7m - 8 = 3 + (-7) + m
Combining like terms on the right, we have
-7m - 8 = -4 + m
Writing the equation with the variable first on the right hand side, we have
-7m - 8 = m - 4
What does a represent?
A.foci
B. Minor axis
C. Major axis
S. Vertices.
Combine like terms to simplify the expression. 5x + 4 + 2x + 5
7x+9
5x+2x= 7x
5+4=9
7x + 9 is the result when combining like terms.
Answer:
7x+9
Step-by-step explanation:
Add the numbers
5x + 4 + 2x + 5
5x+9+2x
Combine like terms
5x+9+2x
7x+9
Solution:
7x+9
Write the numerical expression for the product of 8 and the sum of 9 and 11.3. Then evaluate it.
Solution: The numerical expression is [tex]8\times (9+11.3)[/tex] and the value of this expression is 162.4.
Explanation:
The sum of 9 and 11.3 is written as [tex](9+11.3)[/tex].
The product of 8 means the expression should multiply by 8.
According to the given information the the product of 8 and the sum of 9 and 11.3 is written as [tex]8\times (9+11.3)[/tex].
To evaluate the value of the expression first we have to add 9 and 11.3 after that multiply the result by 8.
[tex]8\times (9+11.3)=8\times (20.3)\\8\times (9+11.3)=162.4[/tex]
Therefore, the numerical expression is [tex]8\times (9+11.3)[/tex] and the value of this expression is 162.4.
Answer:
162.4
Step-by-step explanation:
To write the numerical expression for the product of 8 and the sum of 9 and 11.3 we need to follow these steps:
Sum of 9 and 11.3 is given as follows:
[tex](9+11.3)[/tex]
Now the product of 8 and the sum of 9 and 11.3 is:
[tex]8(9+11.3)[/tex]
So the required expression is:
[tex]8(9+11.3)[/tex]
Solving the above expression we get:
[tex]8(9+11.3)=8(20.3)=8 \times 20.3=162.4[/tex]
Find n so that number sentence below is true and explain your answer, referencing the relevant properties of exponents
Ugh, I hate FLVS. I'm not exactly sure, but i know that 2 to the 12 power is 24, and 2 to the fourth power is 8. Sorry I'm not being very helpful.
I need help solving this question
C.
Combine like terms when adding f(x) and g(x) 2x^2 + x^2 and 1 + (-7) = 3x^2 - 6
212x−34(2x+5)=38
which one
a) x=−458
b) x=−338
c) x=418
d) x=538
Answer:
c
Step-by-step explanation:
Find the original price of a pair of shoes if the sale price is $45 after a 25% discount
$60
$45 is 75% of the original price. 75/3 is 25, so divide 45/3=15. $15 is 1/4 of the original price. 15*4=60
The original price of the pair of shoes is $60.
To find the original price of a pair of shoes, we can use the given information that the sale price is $45 after a 25% discount.
Let's assume the original price of the shoes is "x" dollars.
The discount of 25% means that the sale price is equal to 75% (100% - 25%) of the original price.
Mathematically, we can express this as:
Sale price = Original price * (Discount percentage in decimal form)
$45 = x * (0.75)
To find the original price (x), we divide both sides of the equation by 0.75:
$45 / 0.75 = x
x = $60
Therefore, the original price of the pair of shoes is $60.
To know more about original price:
https://brainly.com/question/731526
#SPJ2
what is the discriminant of p2+6p+9=0
p^2+6p+9=0
The discriminant of a quadratic is the expression inside the radical of the quadratic formula.
b^2−4(ac)
Substitute in the values of
a, b, and c.
6^2−4(1⋅9)
Evaluate the result to find the discriminant.
36-4(9)
36-36
0
The discriminant of the quadratic equation p²+6p+9=0 is zero, suggesting that it has exactly one real, repeated solution.
The discriminant of the quadratic equation p²+6p+9=0 is calculated using the formula D=b²-4ac, where a, b, and c are the coefficients of the quadratic equation ax²+bx+c=0. In this equation, a=1, b=6, and c=9. Substituting these values into the discriminant formula gives us:
D = b² - 4ac
D = (6)² - 4(1)(9)
D = 36 - 36
D = 0
The discriminant is zero, which indicates that the quadratic equation has one real, repeated solution, meaning the parabola touches the x-axis at a single point.
Please help. I will reward brainly
Positive, 72 minus negative 9 is the same thing as 72+9, which equals 81. So the answer is positive
challenge questions 1
9)
[tex]\frac{24z^{5}y^{4}}{3z^{-2}y^{5}} = \frac{24}{3}*\frac{z^{5}}{z^{-2}}*\frac{y^{4}}{y^{5}} = \frac{8}{1} *\frac{z^{5+2}}{1}*\frac{1}{y^{5-4}} = \frac{8z^{7} }{y}[/tex]
11)
(a²b)³ = a²⁽³⁾b¹⁽³⁾ = a⁶b³
12)
The exponent tells you how many places to move the decimal. The positive/negative sign tells you which direction to move the decimal (negative is left, positive is right).
8.4 x 10⁻⁵ move the decimal 5 places to the left = 0.000084
John and his family went out to eat at the bill of the food was $65 and it has a 20% tip what was the total cost other meal including the tip
$78
$65x.20=13
65+13=$78
Solve this linear system by graphing
x-y=6
2x=12+2y
To solve the linear system by graphing, convert the equations to slope-intercept form, plot the lines, and find the point of intersection.
Explanation:To solve the given linear system by graphing, we need to graph both equations on the same coordinate plane and find the point of intersection.
Step 1: Convert both equations into slope-intercept form, y = mx + b.
Step 2: Plot the y-intercepts (b values) of both equations and use the slopes (m values) to draw the lines.
Step 3: The point where the lines intersect is the solution to the system of equations. In this case, the solution is x = 6 and y = 0.
stacey buys 6 pounds of chicken for $39. How much will she pay for 11 more pounds of chicken.
So she pays 6 lb of chicken for $39 then $39/6 = $6.30 is the price per pound.
11lb + 6lb = 17lb total of chicken then multiply it by the price per pound
17($6.50) = $110.50
Final answer:
Stacey will pay $71.50 for 11 more pounds of chicken.
Explanation:
To figure out how much Stacey will pay for 11 more pounds of chicken, we can use the given information that she bought 6 pounds of chicken for $39.
First, we need to find the cost of chicken per pound. To do this, we divide the total cost of chicken ($39) by the number of pounds (6). So, $39 / 6 = $6.50 per pound.Next, we can calculate the cost of 11 more pounds of chicken by multiplying the cost per pound ($6.50) by the number of pounds (11). So, $6.50 * 11 = $71.50.Therefore, Stacey will pay $71.50 for 11 more pounds of chicken.
Martha earns $12.47 per hour. John makes 3 times as much as Martha. How much does John earn per hour?
A.$36.00
B.$37.21
C.$37.41
D.$36.41
PLEASE HELP ME ASAP
The answer is C.37.41
Hanna walks 1 2/3 miles to school. After school she walks 1 1/2 mikes to work. How many miles does she walk before and after school?
Hanna walks a total of 3 1/6 miles before and after school.
To find how many miles Hanna walks before and after school, we can add the distances she walks to school and to work.
Distance to school = 1 2/3 miles
Distance to work = 1 1/2 miles
To find the total distance Hanna walks before and after school, add the two distances:
Total distance = 1 2/3 + 1 1/2
To add these fractions, we need to convert them to have a common denominator, which is 6:
1 2/3 = (3/3 + 2/3) = 5/3
1 1/2 = (3/2)
Now, we can add the fractions:
Total distance = 5/3 + 3/2
To add these fractions, we need to have a common denominator, which is 6:
Total distance = (5/3) * (2/2) + (3/2) * (3/3)
Total distance = 10/6 + 9/6
Now, add the fractions:
Total distance = 19/6
We can simplify this fraction:
Total distance = 3 1/6 miles
So, Hanna walks a total of 3 1/6 miles before and after school.
To know more about miles click here :
https://brainly.com/question/14997853
#SPJ2
3y^2/9y^4 state restrictions and simplify
Step 1. Take out the constants
3/9 y^2y^4
Step 2. Simplify 3/9 to 1/3
1/3 y^2y^4
Step 3. Simplify
y^2y^4/3
Step 4. Use the Product Rule
y^2 + 4/3
Step 5. Simplify 2 + 4 to 6
y^6/3
write each percent as a decimal 89% 100% 0.01%
Miss Kincaid is 65 inches of ribbon is your post to instantly 5 inches of ribbon how many students get a 5 inch piece of ribbon
To determine the number of 5-inch pieces of ribbon that can be obtained from a 65-inch ribbon, divide the total length by the length of each piece. So, 13 students can each get a 5-inch piece of ribbon from the 65-inch ribbon.
Explanation:To determine how many 5-inch pieces of ribbon can be obtained from 65 inches of ribbon, we divide the total length of the ribbon by the length of each piece. So, we divide 65 by 5:
Therefore, 13 students can each get a 5-inch piece of ribbon from the 65-inch ribbon.
Learn more about Dividing Lengths here:https://brainly.com/question/7456580
#SPJ2
q-r=r, for r formula for the variable
Find f if f(x)=23; 23= x²+7
I really need some help so please help me!!!
I'll mark brainliest for the best answer please!!!
here is the options
2.50
20
the daily profit of the taxi cab driver
the initial fee before any miles are traveled
3
the cost per mile traveled
a baseball coach bought some bats and gloves for the school's baseball team.the bats cost $20 to $35,and gloves cost $30 to $60.which of this does not represent a reasonable total purchase price for 15 bats and 12 gloves
A.$1,350
B.$890
C.$1,200
D.$705
Max cost of 15 bats = 15 x 35 = $535
Min cost of 15 bats = 15 x 20 = $300
Max cost of 12 gloves = 12 x 60 = $720
Mix cost of 12 gloves = 12 x 30 = $360
Min total cost = 360 + 300 = $660
Max total cost = 535 + 720 = $1255
The range is from $660 to $1255
=============> Answer (A) is out of the range
value of 3x^2 +4y^2 if x=2, y=1, and z= -3
[tex]3x^2+4y^2\\\\\text{Put the values of x=2, y=1 and z=-3 to the expression:}\\\\3(2^2)+4(1^2)=3(4)+4(1)=12+4=16[/tex]
Substituting the provided values of x and y into the equation 3x^2 +4y^2 gives a final result of 16.
Explanation:The question is asking for the value of the mathematical expression 3x^2 +4y^2 when x is 2 and y is 1. To find this, we substitute the values of x and y into the expression.
Substitute x = 2 into the equation: 3*(2)^2 = 3*4 = 12 Substitute y = 1 into the equation: 4*(1)^2 = 4*1 = 4 Add the results: 12 + 4 = 16
Therefore, the value of 3x^2 +4y^2 when x=2 and y=1 is 16.
Learn more about Substitution into expression here:https://brainly.com/question/37676786
#SPJ3
Which expression is equivalent to 3/4 - 1/2?
Lamar is solving the equation x2−12x=−6 by completing the square. Which shows Lamar's next step and the solution to the equation?
To solve the equation x²−12x=−6, Lamar should first move the constant to the other side and complete the square, leading to x = 6 ±√30. This equation, which is a type of quadratic or second-order polynomial, may have two solutions, a typical characteristic of such equations.
Explanation:The equation presented is x²−12x=−6. To solve this equation by completing the square, we first move the constant term to the other side, which leads to x² - 12x = -6, or x² - 12x + 36 = -6 + 36. We added 36 on both sides because (12/2)² = 36, which is a step in completing the square for the equation. Thus, we have (x-6)² = 30. Now, solve for x: x - 6 = ±√30, so x = 6 ±√30.
This method, known as completing the square, is a typical approach to solving quadratic equations. The general quadratic equation ax²+bx+c = 0 can also be solved using the quadratic formula -b ± √(b² - 4ac) / 2a. With both methods, remember that a quadratic equation will usually have two solutions, as it is a second-order polynomial.
Learn more about Completing the Square here:https://brainly.com/question/4822356
#SPJ12
what is the answer
−2=6/7p
Isolate the p. Note the equal sign. What you do to one side, you do to the other. Multiply 7/6 to both sides
(-2)(7/6) = (6/7)(7/6)p
p = (-2)(7/6)
Multiply -2 and 7, then divide by 6
p = (-2 x 7)/6
p = -14/6
Divide
p = ~-2.33 (rounded)
-2.33 is your answer
hope this helps
Hello there!
[tex]-2=6/7p\\[/tex]
Explanation:
↓↓↓↓↓↓↓↓↓↓
First you had to switch sides.
[tex]\frac{6}{7}p=-2[/tex]
Then you multiply by 7 from both sides of the equation.
[tex]7*\frac{6}{7}p=7(-2)[/tex]
Simplify
[tex]6p=-14[/tex]
Divide by 6 from both sides of the equation.
[tex]\frac{6p}{6}=\frac{-14}{6}[/tex]
Simplify it should be the correct answer.
[tex]p=-\frac{7}{3}[/tex]
Answer⇒⇒⇒⇒⇒p=-7/3
Hope this helps!
Thank you for posting your question at here on Brainly.
Have a great day!
-Charlie
The dimensions of a rectangle can be given by x+7 and x+2. If the area of the rectangle is 66 square inches, what are the dimensions of the rectangle?
to solve for the dimensions (x+7)(x+2)=66,
we can first use the foiling method to simplify the left side.
x^2 + 2x + 7x + 14 = 66
x^2 + 9x + 14 = 66
now, subtract 66 from both sides.
x^2 + 9x - 52 = 0
now, split this into two parentheses.
(x + 13)(x - 4)
since the root of -13 would give you negative values, x=4. This means that the dimensions of the rectangle are 11 and 6.
The dimensions of the rectangle is 11 by 6 inches
How to determine the dimensions?The dimensions are given as:
x + 7 and x + 2
The area is given as:
Area = 66
The area of a rectangle is:
Area = Length * Width
So, we have:
(x + 7) * (x + 2) = 66
Express 66 as 11 * 6
(x + 7) * (x + 2) = 11 * 6
By comparison, we have:
x + 7 = 11 and x + 2 = 6
Solve for x
x = 4 and x = 4
Substitute 4 for x in x + 7 and x + 2
x + 7 = 4 + 7 = 11
x + 2 = 4 + 2 = 6
Hence, the dimensions of the rectangle is 11 by 6 inches
Read more about areas at:
https://brainly.com/question/24487155
Answer any of these questions and still get a good rating if you are correct. (Also this is multiplication with fractions)
1.What is the product in simplest form?
−8/9⋅5/6
2.What is the product?
Enter your answer as a fraction, in simplified form, in the box.
−4/5⋅10/16
3.(−2.1)⋅(−1.4)